THE ATMOSPHERE OF FAMILY LIFE AS AN IMPORTANT CONDITION FOR OPTIMIZING FAMILY EDUCATION ON THE EXAMPLE OF THE FUNCTIONING OF FOSTER FAMILIES IN THE CITY OF SZCZECIN - Kazubowska, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The family, influencing a child in the course of everyday life, has many mechanisms at its disposal, which it uses intentionally and unintentionally. The basic value of a family home is a unique atmosphere, a climate specific to each family, in which it organizes conditions for the child's development in all its areas and personality development. In addition, the atmosphere of family life significantly contributes to building the emotional balance of the child, protects it against various unfavorable phenomena and situations, and builds the child's awareness of himself as a person. The atmosphere of family life is not an easy phenomenon to define. It consists of many factors, such as internal factors, such as the personality of the mother and father, mutual coexistence between family members. Another group of factors are those of an external nature, for example the size of the family, its economic and social status, place of residence. The first part of the text is a discussion of the atmosphere of family life in the light of pedagogical and psychological literature, indicating various approaches, their specificity and its importance in optimizing upbringing in a family. The empirical part focuses on the description of the atmosphere of family life and its specificity in foster families operating in the city of Szczecin. Here, particular attention was paid to the types of atmosphere in these families, its conditions and importance for the optimal development of a child. The final part of the text consists of the final conclusions and conclusions resulting from the research on the practice of working with families, including foster families, as well as with families of children in this form of foster care.